Impact of Generative AI on Student Learning in Higher Education using Robust Assessment Metrics Framework - Adesola M. Falade; Ayobami E. Mesioye (PT. Teknologi Futuristik Indonesia, 2026)
The rapid emergence of Generative Artificial Intelligence (GAI) has transformed the landscape of higher education, influencing pedagogy, assessment, and student learning experiences. Despite its widespread adoption, a significant research gap persists regarding the empirical measurement of its impact on specific learning outcomes. While GAI tools are widely adopted, existing assessment frameworks often fail to distinguish between machine-generated efficiency and genuine cognitive development. This study addresses this gap by developing the Robust Assessment Metrics Framework (RAMF), evaluated through a mixed-methods approach involving students and faculty (N=295) at McPherson University. Quantitative findings reveal a significant